(untitled) (diségno, 2026)
The UID Summer School 2025, themed Il Disegno Virtuale del Reale, was conceived as a high-level educational and research experience dedicated to exploring the relationships between representation, technology, and critical interpretation of the built heritage, between symbolism and iconography. [read more]